A Review of Commitment Savings Products in Development Countries - Nava Ashraf; Nathalie Gons; Dean S. Karlan; Wesley Yin (Asian Development Bank (ADB), 2003)
Many financial institutions in developing countries offer savings products. Yet, little has been done to assess systematically and quantitatively the relative merits of different product designs. This paper first examines different designs that provide incentives to clients to commit to save. Mechanisms are divided into deposit side mechanisms that help clients make regular deposits, and withdrawal-side mechanisms that help clients restrict the use of their funds except for well-planned uses or emergencies. Then, using results from a short web-based survey of microfinance instititutions, we describe different commitment savings products in use around the world.
hdl:11540/1969
Keywords: 330; Sparen; Einlagengeschäft; Zahlungsverkehr; Entwicklungsländer